Analysis of the Relationship Between Motivation and Learning Outcomes of Chinese Language Education Students Class of 2022 Semarang State University in the Chuji Hanyu Xiezuo Xia Course - Listianto, Ridwan; Siregar, Sheyra Silvia; Marsuki, Ria Riski (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2025)
This study aims to analyse the relationship between motivation and learning outcomes of Chinese language education students in the 2022 batch of Semarang State University in the Chuji Hanyu Xiezuo Xia course". It is hoped that this research can help to identify university students' Chinese learning motivation, especially in basic Chinese writing courses or (初级汉语写作下 Chūjí Hànyǔ Xiězuò Xià). This study uses a quantitative approach, this study aims to determine the effect between the independent variable, namely the learning motivation of Chinese language education students class of 2022 on the dependent variable, namely the value or learning outcomes (UAS) in the Chuji Hanyu Xiezuo Xia course. The significance value (Sig. 2-tailed) of 0.008 indicates that the correlation results are statistically significant. In hypothesis testing, since the sig value (0.008) is smaller than 0.05, there is a significant relationship between learning motivation and learning outcomes. This, the data shows that there is a  relationship between learning motivation and learning outcomes in Chinese Language Education students class of 2022 at Semarang State University in the Chuji Hanyu Xiezuo Xia course. There is a relationship between learning motivation and learning outcomes in Chinese Language Education students class of 2022, Semarang State University in Chuji Hanyu Xiezuo Xia course.